AUTOMATIZATION OF WORKSTATIONS PREPARATION IN LOCAL COMPUTER NETWORKS - Skrupskiy, S. U.; Markin, A. G.; Skrupskaya, L. S. (Radio Electronics, Computer Science, Control, 2010)
Methods of workstations preparation in local computer networks are analyzed. Time expenditure for different methods is calculated, the most effective method is determined.